Pemikiran Syekh Mahmud Mukhtar dalam Kitab Adab Al-Muta'alim Ma'a Al-Mu'alim atas Pembentukan Karakter Peserta Didik: (Studi di SMP IT Al Burhany Kabupaten Cirebon) - Amirudin, Amirudin; Jamaludin, Jamaludin (Permata : Jurnal Pendidikan Agama Islam, 2024)
The background of this paper is the current condition of moral degradation of students due to various factors that cause it. Therefore, the results of this research are expected to perfect the concept of student adab to teachers that already exist in the realm of Islamic education. The type of research used by researchers is library research, because this research aims to collect information and data by requiring assistance from various materials that can be obtained from libraries, such as books, records, manuscripts, magazines, documents, historical stories and so on. Then this research uses a concept study research approach or the thoughts of figures and the data sources used are primary and secondary. This research is descriptive analytical in nature, namely research that describes what is the idea in the book of Adabul Muta'allim Ma'al Mu'allim by Sheikh Mahmud Mukhtar Bode about student adab to the teacher. While the analysis method in this research is content analysis, which is research in the form of in-depth discussion of the content of written information. The results of this study reveal that Sheikh Mahmud Mukhtar Bode has thoughts about the manners of a student towards the teacher as stated in his book “Adab al-Muta'allim ma'a al-Mu'allim”, namely: Student's manners towards the teacher, the manners of learning, the manners of choosing a study partner, the path to world-afterlife happiness, scientific sanad, and bid'ah in religion. In addition, Sheikh Mahmud Mukhtar Bode offers that the key to success in forming the characteristics of students includes following the right and good teacher and the right and good learning intentions such as those in Al-Burhany Bode IT Junior High School.Keyword : Sheikh Mahmud Mukhtar; Adab Al-Muta'alim Ma'a Al-Mu'alim; Character Building